1992
DOI: 10.1093/infdis/166.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor 9 Deficiency in Serum of Human Neonates

Abstract: The serum concentration of complement factor C9 (C9) was 260 +/- 47 micrograms/ml (+/- SE) in 14 mothers and less than 42 micrograms/ml in each of their 14 neonates. During incubation for 60 min, 11 of 14 maternal sera and 3 of 14 neonatal sera reduced the survival of Escherichia coli O7w:K1:NM to less than 20% of the original inoculum (P less than .03). Eleven neonatal sera did not kill the bacteria. Supplemental C9 (60 micrograms/ml) enhanced the bactericidal capacity of 10 neonatal sera. 125I-labeled C9 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 27 publications
4
27
0
4
Order By: Relevance
“…This observation was due at least in part to diminished concentrations of C9 in the sera of neonates (7,12). The studies reported herein revealed that the onset of a detectable decline in the number of surviving bacteria was delayed during incubation with pooled neonatal serum (Figs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This observation was due at least in part to diminished concentrations of C9 in the sera of neonates (7,12). The studies reported herein revealed that the onset of a detectable decline in the number of surviving bacteria was delayed during incubation with pooled neonatal serum (Figs.…”
Section: Discussionmentioning
confidence: 61%
“…To determine the mechanisms by which supplemental C9 accelerates bacterial killing in neonatal serum, we used a radiobinding assay and immunogold electron microscopy. Previous studies revealed that radiolabeled supplemental C9 was deposited onto E. coli by neonatal serum (12). However, these studies did not determine whether the supplemental C9 was displacing intrinsic C9 from the bacterial surface or whether the total amount of C9 deposited was enhanced.…”
Section: Discussionmentioning
confidence: 96%
“…Por outro lado, em recém-nascidos a termo, a produção de mediadores que contribuem para o recrutamento de neutró-filos para o local da infecção varia de 25% a 50% daquela de adultos (GM-CSF, TNF, IL-8, leucotrieno B4), enquanto a produção de G-CSF e IL-1 é semelhante à do adulto 9 . Adicionalmente, recém-nascidos a termo e, particularmente, recém-nascidos pré-termo têm deficiências em ambas as vias do sistema complemento e em fibronectinas, sendo que as frações da via alternativa do complemento possuem menores concentrações do que as da via clássica 12 . Em conseqüência, ocorre prejuízo na lise de bactérias (C9), especialmente as gram-negativas, e diminuição da opsonização (C3b), principalmente para as bactérias capsuladas 12 .…”
Section: Colonização Infecção E Mecanismos De Defesa De Recém-nascidosunclassified
“…Adicionalmente, recém-nascidos a termo e, particularmente, recém-nascidos pré-termo têm deficiências em ambas as vias do sistema complemento e em fibronectinas, sendo que as frações da via alternativa do complemento possuem menores concentrações do que as da via clássica 12 . Em conseqüência, ocorre prejuízo na lise de bactérias (C9), especialmente as gram-negativas, e diminuição da opsonização (C3b), principalmente para as bactérias capsuladas 12 .…”
Section: Colonização Infecção E Mecanismos De Defesa De Recém-nascidosunclassified
“…Πιο συγκεκριμένα, τα νεογνά διαθέτουν εξαιρετικά χαμηλά επίπεδα του μορίου C9, το οποίο θεωρείται καταλυτικό στη δημιουργία του MAC και συνεπώς καθίστανται επιρρεπή σε λοιμώξεις από Neisseria [27].…”
Section: μη κυτταρικα στοιχεια της φυσικης ανοσιας του νεογνουunclassified